2019
DOI: 10.20546/ijcmas.2019.807.206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Number of Seedling per Hill on Growth and Yield of Black Scented Rice (Oryza sativa L.) Variety ‘Chakhao Poireiton’ under Manipur Condition

Abstract: Field experiments were conducted during kharif 2014 and 2015 to study the effect of age and number of seedling per hill on growth and yield of black scented rice (Oryza sativa L.) variety "Chakhao Poireiton' under Manipur condition to find out the suitable age of seedling and number of seedling per hill. The experiment consists of four seedling age viz., A 1 -15 days old seedling; A 2 -25 days old seedling; A 3 -35 days old seedling; A 4 -45 days old seedling and four number of seedlings per hill viz., S 1 -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…2015; Devi et al, 2019;Promsomboon, 2019;Singh et al, 2020). The larger number of seedlings/hill increases competition for tiller formation, solar radiation interception, sunshine reception, nutrient uptake, photosynthesis rate and other physiological phenomena which eventually affect the growth and development of plants (Bozorgi et al, 2011).…”
Section: Original Research Articlementioning
confidence: 99%
“…2015; Devi et al, 2019;Promsomboon, 2019;Singh et al, 2020). The larger number of seedlings/hill increases competition for tiller formation, solar radiation interception, sunshine reception, nutrient uptake, photosynthesis rate and other physiological phenomena which eventually affect the growth and development of plants (Bozorgi et al, 2011).…”
Section: Original Research Articlementioning
confidence: 99%
“…Verification of the conclusions was accomplished by demonstration trials on the farm, which revealed that mechanically hill-seeded rice at such a density produced grain yields that were comparable to or significantly greater than transplanted rice. Devil et al [17] observed that the sky-high grain yield (1719 kg ha-1) in the 3 seedlings hill-1 (S-3) treatment was significantly more than all other treatments, whereas the lowest grain yield (1346 kg/ha) was in the 1 seedlings hill-1 treatment (S-1). Transplanting 15-day-old seedlings with 2 seedlings hill-1 (S-2) treatment yields the highest gross return (Rs 1.08,945 ha-1) and net return (Rs 69,536 ha-1) as well as the highest B:C ratio (1.76).…”
Section: Introductionmentioning
confidence: 99%